Physical confinement induces malignant transformation in mammary epithelial cells. (October 2019) - Lu, Yen-Chun; Chu, Tinyi; Hall, Matthew S.; Fu, Dah-Jiun; Shi, Quanming; Chiu, Alan; An, Duo; Wang, Long-Hai; Pardo, Yehudah; Southard, Teresa; Danko, Charles G.; Liphardt, Jan; et al.
Abstract: The physical microenvironment of tumor cells plays an important role in cancer initiation and progression. Here, we present evidence that confinement – a new physical parameter that is apart from matrix stiffness - can also induce malignant transformation in mammary epithelial cells. We discovered that MCF10A cells, a benign mammary cell line that forms growth-arrested polarized acini in Matrigel, transforms into cancer-like cells within the same Matrigel material following confinement in alginate shell hydrogel microcapsules. The confined cells exhibited a range of tumor-like behaviors, including uncontrolled cellular proliferation and invasion. Additionally, 4–6 weeks after transplantation into the mammary fad pads of immunocompromised mice, the confined cells formed large palpable masses that exhibited histological features similar to that of carcinomas. Taken together, our findings suggest that physical confinement represents a previously unrecognized mechanism for malignancy induction in mammary epithelial cells and also provide a new, microcapsule-based, high throughput model system for testing new breast cancer therapeutics.